Pengaruh Kinerja Keuangan Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2022-2024 - Hasanah, Hani Nur; Pabulo, Azfa Mutiara Ahmad (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The purpose of this research is to examine manufacturing companies listed on the Indonesia Stock Exchange in the consumer services and retail subsectors from 2022 to 2024 and to analyze how liquidity, solvency, and profitability affect dividend policy. Dividend distribution often places companies in financial difficulty, preventing them from expanding as quickly as shareholders desire. This issue therefore becomes the focus of this study. Fifteen companies and forty-eight observations were selected as samples using a purposive sampling technique based on specific criteria. Statistical information was obtained from publicly available annual financial reports published by the IDX. Data analysis was carried out using SPSS 27 through multiple linear regression and classical assumption tests to ensure model validity. The results indicate that solvency has a significant effect on dividend policy (t = -3.479; Sig. = 0.002), whereas liquidity (Sig. = 0.141) and profitability (Sig. = 0.705) have no significant effect. Simultaneously, the three variables have a significant influence (F = 4.318; Sig. = 0.012) with an R² value of 0.332, meaning that 33.2% of the variation in dividend policy is explained by these three factors. Based on these findings, debt-based financing mechanisms play a more crucial role in determining post-pandemic dividend policy. Investors, researchers, and management can all benefit from these results by gaining a better understanding of the financial variables that influence dividend policy.